Island Detection Communication in IEC61850 Grid Controller by Utilizing 2oo3 Architecture to Improve Redundancy and Reliability - Shaikh, M. A.; Pathan, E.; Rabani, M. I.; Goli, S. B.; Qureshi, A. A.; Shahid, M.; Pathan, F.; Khan, M. H. (Engineering, Technology & Applied Science Research, 2021)
After large-scale photovoltaic (PV) and wind power integration with the national grid, the island grid detection is a crucial technique that identifies when a grid should be considered as dead. This logic is built in an IEC61850 grid controller which mainly depends on the bus bar scheme and fault type. It becomes more complex when the ½ circuit breaker scheme is utilized. The lack of communication redundancy causes island mal-operation due to the substation’s DC supply failure. In order to avoid such mal-operation discrepancies, this paper investigates the conventional islanding detection method. Then, an advanced IEC61850 grid controller 2oo3 architecture is proposed for islanding detection, based on SAS redundant communication which improves reliability. However, even if there is an interface communication failure, the power plant control center can still detect the islanding through the proposed IEC61850 grid controller and SCADA IEC60870-5-101/104 gateways integration. This method has the tendency of full supervision of the entire grid and perfect logical judgment by plant operation staff. This feasible and the proposed redundant communication architecture can play a decisive role for power system network stability in order to avoid system blackout.